A cis‐acting bidirectional transcription switch controls sexual dimorphism in the liverwort. (4th January 2019) - Hisanaga, Tetsuya; Okahashi, Keitaro; Yamaoka, Shohei; Kajiwara, Tomoaki; Nishihama, Ryuichi; Shimamura, Masaki; Yamato, Katsuyuki T; Bowman, John L; Kohchi, Takayuki; Nakajima, Keiji
Abstract: Plant life cycles alternate between haploid gametophytes and diploid sporophytes. While regulatory factors determining male and female sexual morphologies have been identified for sporophytic reproductive organs, such as stamens and pistils of angiosperms, those regulating sex‐specific traits in the haploid gametophytes that produce male and female gametes and hence are central to plant sexual reproduction are poorly understood. Here, we identified a MYB‐type transcription factor, MpFGMYB, as a key regulator of female sexual differentiation in the haploid‐dominant dioicous liverwort, Marchantia polymorpha . MpFGMYB is specifically expressed in females and its loss resulted in female‐to‐male sex conversion. Strikingly, Mp FGMYB expression is suppressed in males by a cis ‐acting antisense gene SUF at the same locus, and loss‐of‐function suf mutations resulted in male‐to‐female sex conversion. Thus, the bidirectional transcription module at the Mp FGMYB/SUF locus acts as a toggle between female and male sexual differentiation in M. polymorpha gametophytes. Arabidopsis thaliana Mp FGMYB orthologs are known to be expressed in embryo sacs and promote their development. Thus, phylogenetically related MYB transcription factors regulate female gametophyte development across land plants. Synopsis: The basal land plant liverwort spends most of its life cycle in a haploid state with distinct male and female morphology. A conserved MYB‐type transcription factor regulates the sexual differentiation process, suggesting a shared origin for gamete formation in plants. The autosomal MpFGMYB gene promotes female sexual differentiation in the liverwort Marchantia polymorpha . MpFGMYB belongs to a MYB subfamily whose members are known to regulate female gametophyte development in Arabidopsis thaliana . Expression of MpFGMYB is suppressed in males by its antisense gene SUF in cis . Loss‐of‐function mutations of either MpFGMYB in females or SUF in males leads to near‐complete sex conversion phenotypes. Abstract : Female sexual differentiation in a basal land plant is determined by an antisense RNA‐regulated MYB‐type transcription factor, whose conservation in vascular plants suggests shared principles for gamete formation.